2004
DOI: 10.1210/jc.2003-030908
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate in Primary Hyperparathyroidism: A Double-Blind, Randomized, Placebo-Controlled Trial

Abstract: Primary hyperparathyroidism (PHPT) is often associated with reduced bone mineral density (BMD). A randomized, double-blind, placebo-controlled trial was conducted to determine whether alendronate (ALN), 10 mg daily, maintains or improves BMD in patients with PHPT. Eligible patients had asymptomatic PHPT and did not meet surgical guidelines or refused surgery. Forty-four patients randomized to placebo or active treatment arms were stratified for gender. At 12 months, patients taking placebo crossed over to acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
1
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(149 citation statements)
references
References 17 publications
(32 reference statements)
9
127
1
11
Order By: Relevance
“…After 1 year, patients receiving placebo, started on alendronate and similar changes in BMD were observed in the 2 nd year. Bone turnover markers decreased with the use of alendronate and serum PTH, phosphate and ionized calcium levels did not change during the study (171) (A-1B).…”
Section: Bisphosphonatesmentioning
confidence: 97%
See 1 more Smart Citation
“…After 1 year, patients receiving placebo, started on alendronate and similar changes in BMD were observed in the 2 nd year. Bone turnover markers decreased with the use of alendronate and serum PTH, phosphate and ionized calcium levels did not change during the study (171) (A-1B).…”
Section: Bisphosphonatesmentioning
confidence: 97%
“…Data from randomized controlled studies have consistently demonstrated that oral alendronate decreases bone turnover and increases BMD in patients with mild PHPT, although the effects on serum calcium have been inconsistent (169)(170)(171) (A-1B).…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…They also slightly increase the bone mineral density parameters at the lumbar spine and hip but not at the distal radius. Their possible long-term disadvantages must not be overlooked (62,63,64).…”
Section: )mentioning
confidence: 99%
“…Unfortunatelly, none of this treatment have been evaluated in clinical assays neither in hyperparathyroidism nor HPHPT ). Only alendronate treatment was shown to improve BMD in lumbar spine of patients with primary hyperparthyroidism without changes in calcium levels to a degree comparable both to their effects in eucalcemic populations (Khan et al, 2004) What is more, fracture outcome date are not available until now with any of the treatments evaluated.…”
Section: Medical Treatment Of Asymptomatic Hptmentioning
confidence: 99%